2018
DOI: 10.1016/j.trci.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Highly specific and selective anti‐pS396‐tau antibody C10.2 targets seeding‐competent tau

Abstract: IntroductionThe abnormal hyperphosphorylation of the microtubule-associated protein tau plays a crucial role in neurodegeneration in Alzheimer's disease (AD) and other tauopathies.MethodsHighly specific and selective anti-pS396-tau antibodies have been generated using peptide immunization with screening against pathologic hyperphosphorylated tau from rTg4510 mouse and AD brains and selection in in vitro and in vivo tau seeding assays.ResultsThe antibody C10.2 bound specifically to pS396-tau with an IC50 of 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…There has been significant progress in humanizing animal tauopathy models; by injecting patient-derived tau fibrils as seeds into rodent brains, the aggregation, histopathological lesions, and cell-type specificity of the patient can be recapitulated. Such models may provide better translatability to study the mechanisms of tau pathology in vivo and are increasingly used to test novel therapeutics (148,149). Important outstanding questions that can be studied with these models are, for example, how microglia, astrocytes, and other cell types are involved in the progression of tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant progress in humanizing animal tauopathy models; by injecting patient-derived tau fibrils as seeds into rodent brains, the aggregation, histopathological lesions, and cell-type specificity of the patient can be recapitulated. Such models may provide better translatability to study the mechanisms of tau pathology in vivo and are increasingly used to test novel therapeutics (148,149). Important outstanding questions that can be studied with these models are, for example, how microglia, astrocytes, and other cell types are involved in the progression of tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent evidence that the transneuronal propagation of pathological Tau underlies the progression of Tauopathy in AD. Blocking Tau spreading using Tau antibodies therefore represents an attractive therapeutic strategy for AD, which is currently being pursued by several groups worldwide (Bright et al, 2015, Yanamandra et al, 2015, Albert et al, 2019, Rosenqvist et al, 2018, Vandermeeren et al, 2018). Here we demonstrate for the first time that in Tau K+100mM: 0.2431, veh: 0.7968; 2h: K+100mM: 0.7881, veh: 0.8917; 3h: K+100mM: 0.0592, veh: 0.1777; 4h: K+100mM: 0.5616, veh: 0.6041; 5h: K+100mM: 0.3720, veh: 0.7897; 6h: K+100mM: 0.8825, veh: 0.2753; 7h: K+100mM: 0.2564, veh: 0.2259 conv, 0.0629, cOFM, 0.9185;4h: conv, 0.0550, cOFM, 0.9847;6h: conv, 0.0651, cOFM, 0.1544;8h: conv, 0.1084, cOFM, 0.9581;10h: conv, 0.1460, cOFM, 0.8370;12h: conv, 0.4352, cOFM, 0.2087;14h: conv, 0.5078, cOFM, 0.3067;16h: conv, 0.7198, cOFM, 0.4510;18h: conv, 0.8739, cOFM, 0.6409;20h: conv, 0.1719, cOFM, 0.0892;22h: conv, 0.5585, cOFM, 0.2094;24h: conv, 0.5777, cOFM, 0 group, p-values.…”
Section: Discussionmentioning
confidence: 99%
“…Because many tau kinases are involved in physiological intracellular signaling pathways, tau kinase inhibitor development appropriately avoiding physiological on targets might be difficult. Meanwhile, based on the view that a specific phosphorylation pattern is required to induce tau self-assembly (Fichou et al, 2019 ; Lauretti and Praticò, 2020 ), several groups have reported data indicating that the phospho-S396/404 epitope constitutes an effective therapeutic target (Boutajangout et al, 2011 ; Gu et al, 2013 ; Liu et al, 2016 ; Rosenqvist et al, 2018 ). Thus, studies have used immunotherapy targeting tau phosphorylation at S396/404.…”
Section: Tau-targeted Therapiesmentioning
confidence: 99%
“…The monoclonal antibody Lu AF87908 binds to the phospho-S396 region of tau (Sandusky-Beltran and Sigurdsson, 2020 ). A preclinical study showed that the original mouse antibody inhibited tau propagation induced by exposure of tau transgenic brain lysates in vivo and in vitro (Rosenqvist et al, 2018 ). Currently, a phase 1 trial (NCT04149860) is assessing the tolerability of Lu AF87908 in healthy individuals and AD patients (NCT04149860).…”
Section: Tau Clearance and Immunotherapymentioning
confidence: 99%